2018
DOI: 10.1097/rli.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Total and Intracellular Sodium Concentration in Primary Prostate Cancer and Adjacent Normal Prostate Tissue With Magnetic Resonance Imaging

Abstract: Tissue sodium concentration and intracellular sodium concentrations of prostate tumors were quantified, with PZ tumors demonstrating a significantly increased TSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…17 Further investment is needed in training and in standardisation of reporting to reduce inter-rater variability in results and improve inter-rater reliability in reporting for us to fully embrace the benefits that can be conferred by mpMRI triage. 18,19…”
Section: What Is Mpmri?mentioning
confidence: 99%
“…17 Further investment is needed in training and in standardisation of reporting to reduce inter-rater variability in results and improve inter-rater reliability in reporting for us to fully embrace the benefits that can be conferred by mpMRI triage. 18,19…”
Section: What Is Mpmri?mentioning
confidence: 99%
“…Since Trio was shown to be implicated in controlled turnover of invadopodia during cancer cell invasion, it raised the possibility of NALCN involvement in tumorigenesis (Kwiatkowska et al, 2012;Moshfegh et al, 2014). Furthermore, the elevated tissue Na + concentration has been found to be a highly specific in vivo indicator of malignancy, which can be, at least in part, provided by sustained NALCN-mediated Na + influx (Barrett et al, 2018;Bartha et al, 2008;Haneder et al, 2015;Henzler et al, 2012;Huang et al, 2018;Jacobs et al, 2011;Laymon et al, 2012;Leslie et al, 2019;Ouwerkerk et al, 2003Ouwerkerk et al, , 2007Zaric et al, 2016). Given the tight coupling between Na + and Ca 2+ signaling (Verkhratsky et al, 2018), we hypothesized that in metastatic cancer cells NALCN could provide signaling input encouraging the cell invasion via intracellular Ca 2+ events.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously shown that the total tissue sodium concentration (TSC) and intracellular sodium (IC) are significantly higher in the normal peripheral zone (PZ) of the prostate compared with the transition zone (TZ). [9][10][11] Furthermore, TSC and IC sodium in PZ tumors are higher than in normal PZ, with preliminary evidence suggesting that higher-grade tumors may have a higher sodium concentration compared with lower-grade tumors. 9 Despite the potential significance of 23 Na-MRI for imaging the prostate, one of the major limitations for more widespread acceptance is the requirement for a dedicated endorectal coil tuned to the frequency for 23 Na.…”
mentioning
confidence: 98%
“…[9][10][11] Furthermore, TSC and IC sodium in PZ tumors are higher than in normal PZ, with preliminary evidence suggesting that higher-grade tumors may have a higher sodium concentration compared with lower-grade tumors. 9 Despite the potential significance of 23 Na-MRI for imaging the prostate, one of the major limitations for more widespread acceptance is the requirement for a dedicated endorectal coil tuned to the frequency for 23 Na. However, there has been notable recent interest in multinuclear imaging of the prostate driven by the translation of hyperpolarized carbon-13 MRI ( 13 C-MRI) as a method for noninvasive assessment of tissue metabolism in humans.…”
mentioning
confidence: 98%
See 1 more Smart Citation